Opposing roles of PKA and EPAC in the cAMP-dependent regulation of schwann cell proliferation and differentiation [corrected]. - Ketty Bacallao (Public Library of Science (PLoS), 2013)
In Schwann cells (SCs), cyclic adenosine monophosphate (cAMP) not only induces differentiation into a myelinating SC-related phenotype, but also synergistically enhances the mitogenic action of growth factors such as neuregulin. To better understand the molecular mechanism by which cAMP exerts these apparently contradictory functions, we investigated the role of the two main effectors of cAMP, protein kinase A (PKA) and the exchange protein activated by cAMP (EPAC), on the proliferation and differentiation of both isolated and axon-related SCs. For these studies, a variety of PKA and EPAC agonists and antagonists were used, including pathway-selective analogs of cAMP and pharmacological inhibitors. Our studies indicated that the activity of PKA rather than EPAC was required for the adjuvant effect of cAMP on S-phase entry, whereas the activity of EPAC rather than PKA was required for SC differentiation and myelin formation. Even though selective EPAC activation had an overall anti-proliferative effect in SCs, it failed to drive the expression of Krox-20, a master regulator of myelination, and that of myelin-specific proteins and lipids, suggesting that EPAC activation was insufficient to drive a full differentiating response. Interestingly, inhibition of EPAC activity resulted in a drastic impairment of SC differentiation and myelin formation but not Krox-20 expression, which indicates an independent mechanism of Krox-20 regulation in response to cAMP. In conclusion, our data supports the idea that the outcome of cAMP signaling in SCs depends on the particular set of effectors activated. Whereas the mitogenic action of cAMP relies exclusively on PKA activity, the differentiating action of cAMP requires a PKA-independent (non-canonical) cAMP-specific pathway that is partially transduced by EPAC.